EFFECTS OF CRYOPRESERVATION AND RELATIVE HUMIDITY ON VIABILITY AND NUTRITIONAL COMPOSITION OF SAINFOIN (ONOBRYCHIS VICIIFOLIA SCOP.) - S. Mohajer; R. M. Taha; M. Mohajer (Journal of Animal and Plant Sciences, 2016)
Changes in seed viability due to environmental conditions are crucial factors to preserve seed germination ability in equatorial zones. Influence of relative humidity (RH) and frozen storage on the seed viability, nutritional compositions, trace metals and macro-nutrientsof three Onobrychisviciifolia varieties (Golpaygan-181, Orumieh-1763 and Gorgan-1601) were investigated. Mean relative humidity of 84% hastened the loss of seed viability during 6 months, while frozen seeds at -20ºC only exerted a minimal deteriorative effect on the germination of seed and vigor index. HPLC profiles differed in peak areas of the two important alkaloids, Berberine and Sanguinarine, in ambient humidity compared with control condition. Accumulation of crude protein (CP) and dry matter digestibility (DMD) were enhanced under ambient humidity and frozen storage in seed cells. Relative humidity indicated positive effects on seed quality by crude fibre (CF) reduction. The atomic spectroscopy analysis confirmed the increment of trace metals ratio (Fe, Mn and Cu) and reduction of macro-nutrients ratio (Ca, P and N) in frozen storage after 6 months. Although vigor index and germination speed were lower in frozen storage seeds compared with control seeds, the notable results can be optimizedin future studies.
Keywords: viability; relative humidity; frozen storage; crude protein; alkaloid